2021
DOI: 10.3892/mmr.2021.12314
|View full text |Cite
|
Sign up to set email alerts
|

miR‑140‑5p alleviates mouse liver ischemia/reperfusion injury by targeting CAPN1

Abstract: Ischemia/reperfusion (I/R)-induced liver injury remains a primary concern in liver transplantation and hepatectomy. Previous studies have indicated that microRNAs (miRs) are involved in multiple pathophysiological processes, including liver I/R. miR-140-5p reportedly inhibits inflammatory responses and apoptosis in several diseases; however, the role of miR-140-5p in liver I/R remains unknown. The present study aimed to investigate the potential role and mechanism of miR-140-5p on liver I/R injury. Mouse liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…To identify the role of miR-140-5p in hepatic IRI, overexpression and knockout mice models were used to compare the results [54]. The study revealed that miR-140-5p is downregulated during hepatic IRI, resulting in an increase in inflammatory markers and cell apoptosis [54].…”
Section: Mirna-140-5pmentioning
confidence: 99%
See 4 more Smart Citations
“…To identify the role of miR-140-5p in hepatic IRI, overexpression and knockout mice models were used to compare the results [54]. The study revealed that miR-140-5p is downregulated during hepatic IRI, resulting in an increase in inflammatory markers and cell apoptosis [54].…”
Section: Mirna-140-5pmentioning
confidence: 99%
“…To identify the role of miR-140-5p in hepatic IRI, overexpression and knockout mice models were used to compare the results [54]. The study revealed that miR-140-5p is downregulated during hepatic IRI, resulting in an increase in inflammatory markers and cell apoptosis [54]. Whenever miR-140-5p is overexpressed in cells, inflammatory cytokines and cellular apoptosis are reduced due to the inhibition of CAPN1 [54].…”
Section: Mirna-140-5pmentioning
confidence: 99%
See 3 more Smart Citations